1992
DOI: 10.1161/01.cir.85.2.526
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tissue-type plasminogen activator during acute myocardial infarction in men. Effect of a prostacyclin analogue.

Abstract: BACKGROUND Coronary reocclusion complicates the thrombolytic therapy of acute myocardial infarction despite the routine use of aspirin. This is consistent with experimental studies demonstrating that multiple agonists, in addition to thromboxane A2, mediate the platelet activation underlying reocclusion. Consequently, a more potent antiplatelet therapy with a broader spectrum of activity than aspirin may be required in this setting. Prostacyclin and its more stable analogue, iloprost, inhibit plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…t "/# b of pamiteplase showed marked prolongation compared with wt-PA, whose half-life in humans is 3 min (Seifried et al 1988, Tanswell et al 1989, Kerins et al 1992. Cl total of pamiteplase was smaller than hepatic blood¯ow, indicating that pamiteplase was a capacity-limited drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…t "/# b of pamiteplase showed marked prolongation compared with wt-PA, whose half-life in humans is 3 min (Seifried et al 1988, Tanswell et al 1989, Kerins et al 1992. Cl total of pamiteplase was smaller than hepatic blood¯ow, indicating that pamiteplase was a capacity-limited drug.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetics of wt-PA in humans have reported that Cl total of immunoreactive and bioactive concentrations ranges from 35± 3 to 41± 2 l.h ± " and from 54± 4 to 74± 1 l.h ± " respectively (Seifried et al 1988, Tanswell et al 1989, Kerins et al 1992. Cl total of immunoreactive and bioactive concentrations of pamiteplase decreased to C 20% those of wt-PA.…”
Section: Discussionmentioning
confidence: 99%